KRIYA KERAMIK: WUJUD, POSISI, DAN PERANNYA DI MASA KINI - Satrio, Akbar Adhi (CORAK, 2012)
This article act as a response for what is kriya especially ceramic craft in nowadays context. Public usually knows about ceramic is limited to traditional terracotta product that they usually found in a craftsmen village or an industrial mass produce ceramic that they always use in their everyday life. Kriya (or craft in the western term) now has grew more not only limited in the scope of tradition or even a mass product only. There are many new small independent studio emerge as a new perception that combine the potential of both industrial and traditional have. The role of educational institutions are producing graduates working in the field of ceramic craft has established a new perception on how it should craft in contemporary ceramics put his position in the midst of globalization. Ultimately concluded that the ceramic craft began to position himself to a wider sphere, not only as a center for craftsmen but also intangible and handicraft industries based independent studio-based designermaker.Keywords : kriya, ceramic, culture, identity